Comparative Study To Evaluate The Efficacy Of Dexmedetomidine (5 Mcg), Nalbuphine (1 Mg), And Magnesium Sulfate (100 Mg) As Adjuvants To 0.75% Hyperbaric Ropivacaine In Subarachnoid Block For Lower Limb Surgery - V Rama Krishna, Tiruvaipathi Lalith; Deepthi, Griddaluru Sindhura; Reddy, Avula Charan Teja; Kumar, Gunapati Chaitanya; Chaitanya, Kandukuru Krishna (Journal of Neonatal Surgery, 2025)
Background: Adjuvants to local anaesthetics in subarachnoid block (SAB) enhance anaesthesia quality and prolong analgesia. This study compares dexmedetomidine, nalbuphine, and magnesium sulfate as adjuvants to hyperbaric ropivacaine. Methods: A randomized, double-blind study was conducted on 90 patients undergoing elective lower limb surgery under SAB. Patients were divided into three groups (n=30): Group D received 5 mcg dexmedetomidine, Group N received 1 mg nalbuphine, Group M received 100 mg magnesium sulfate, each with 3 ml of 0.75% hyperbaric ropivacaine. Onset, duration, regression, analgesia, and adverse effects were recorded. Results: Dexmedetomidine produced the fastest onset and longest duration of block and analgesia. Nalbuphine was intermediate. Magnesium had delayed onset and shortest duration. Dexmedetomidine caused more bradycardia and hypotension. Conclusion: Dexmedetomidine is the most effective adjuvant but needs hemodynamic monitoring. Nalbuphine offers a good efficacy-safety balance. Magnesium sulfate is the least effective in this context.